Interleukin-1β Increases Angptl4 (FIAF) Expression via the JNK Signaling Pathway in Osteoblastic MC3T3-E1 Cells - Noh, J. M.; Shen, C.; Kim, S. J.; Kim, M. R.; Kim, S. H.; Kim, J. H.; Park, B. H.; Park, J. H. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Angiopoietin-like protein 4 (Angptl4), also known as fasting-induced adiopogenic factor (FIAF), has recently been reported to influence bone metabolism. However, there have been few studies on regulatory factors other than hypoxia for Angptl4 in bone, and particularly in osteoblasts. Expression of interleukin-1β (IL-1β), a proinflammatory cytokine, is increased in serum or bone microenvironments in inflammatory bone diseases or estrogen deficient-conditions. The present study was conducted to determine whether Angptl4 expression in osteoblasts is affected by IL-1β and investigate its involvement in MAP kinase signaling pathways. Angptl4 RNA levels were increased by IL-1β treatment in murine MC3T3-E1 osteoblastic cells. Western blotting and immunofluorescent staining showed a corresponding increase in Angptl4 protein. IL-1β treatment of osteoblasts induced phosphorylation of mitogen-activated protein kinases (MAPKs) including extracellular regulated kinases (ERKs), p38, and c-Jun N-terminal kinase (JNK). Furthermore, SP600125, an inhibitor of JNK, significantly blocked the upregulation of Angptl4 by IL-1β. In contrast, treatment with an inhibitor of p38 MAP kinase (SB203580) or an ERK inhibitor (PD98059) produced responses similar to those seen with the DMSO control. Taken together, these results suggest that IL-1β increases Angptl4 expression through a mechanism dependent on the JNK-MAPK signaling pathway in MC3T3-E1 cells.
Keywords: angptl4; osteoblast; interleukin-1beta; MAP kinase signaling system; JNK mitogen-activated protein kinase